(3TQM JGFjI GdUaOjs - (3YHO GdbGOQ Hf eMeO Hf YeQ, CHh GdfLGFH GHf MHjH GdUaOj GdTGaYj,J (B915 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf Yde GdSdhc aQV Yjf HdG NdGa Ydi GdPchQ hGdEfGK hGdYHjO hGdCTQGa EP GdLejY eNdhbhf ddYHGOI s
(3BNQgG (B:s
(3Ef JLO YjHkG aSO GdNdd JHbi YfO GdfGS aj Yjf GdedG Je GdcJGH HYhf Gdedc GdhgGH s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B42 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B300s
Keywords: (3GdJUha hGdBOGH GdTQYjIs